Assessing and enhancing medical students' computer skills: a two-year experience. - Hollander, S (1999)
In 1984, the Association of American Medical Colleges (AAMC) issued recommendations for the reform of medical education. One recommendation was that information sciences be incorporated into the medical curriculum. In fall 1996, a survey was conducted to learn more about computer use by medical students at the Rockford regional site of the University of Illinois at Chicago College of Medicine. The purpose of the survey was to gather information not only about computer skills, but also about overall comfort level in using computers and about expectations for enhancing computer skills while attending medical school. Over a two year period, 208 students representing four classes received this survey in their e-mail. Non-respondents received a follow-up print copy in their student mailboxes. Results, based on a 60% response rate, showed a majority of Rockford students entered medical school with good skills in using e-mail and word processing, but many lacked the skills necessary to search the medical literature or to use computer-assisted instructional programs. Overall, 80% of students expected to learn more about computers while attending medical school. Results contributed to an increased effort to integrate computer applications into the medical curriculum and to use computers as a means of communicating with students.